FORMATION OF SELF-DEVELOPMENT COMPETENCIES IN STUDENTS OF FUTURE TEACHERS - Oppoqxo‘jayev Xojixuja Azimjon o‘g‘li (Galaxy International Interdisciplinary Research Journal, 2023)
This article reveals the pedagogical basis of the concepts of competence and competence, the types and forms of competence, the formation of self-development competences.